2005
DOI: 10.4319/lo.2005.50.1.0169
|View full text |Cite
|
Sign up to set email alerts
|

Exchange between a freshwater embayment and a large lake through a long, shallow channel

Abstract: We analyze the exchange between a weakly forced lacustrine embayment and a large lake through a long, shallow channel. Exchange in the channel is the result of a multiple and subtle balance in which spatial thermal variations (baroclinic forcing), oscillations in the water level (barotropic forcing), bottom friction, diffusion, wind forcing, and the effects of unsteadiness are all important. Temperature gradients across the channel result from differences in thermal inertia of the embayment and lake at seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…For instance Hamblin and He (2003) showed that in a field experiment in the very long 828 m canal that connects Lake Ontario to Hamilton Harbour that only 23% of the observed flows driven by seiche motions had an excursion length greater than that of the channel and so could actually produce flushing of the 20 m deep waters of the Hamilton harbour. Similar remarks were also made by Rueda and Cowen (2005) about the inability of small water level fluctuations to actual drive water excursions in the 480-m-long shipping canal in the 10 m deep Little Sodus Bay. In contrast the Frenchman's Bay channel is only 130 m long, and as the mean depth of the bay is 1.5 m the small amplitude water level fluctuations can lead to flushing on a timescale of weeks.…”
Section: Water Temperature and Water Level Fluctuations Measurementssupporting
confidence: 55%
See 3 more Smart Citations
“…For instance Hamblin and He (2003) showed that in a field experiment in the very long 828 m canal that connects Lake Ontario to Hamilton Harbour that only 23% of the observed flows driven by seiche motions had an excursion length greater than that of the channel and so could actually produce flushing of the 20 m deep waters of the Hamilton harbour. Similar remarks were also made by Rueda and Cowen (2005) about the inability of small water level fluctuations to actual drive water excursions in the 480-m-long shipping canal in the 10 m deep Little Sodus Bay. In contrast the Frenchman's Bay channel is only 130 m long, and as the mean depth of the bay is 1.5 m the small amplitude water level fluctuations can lead to flushing on a timescale of weeks.…”
Section: Water Temperature and Water Level Fluctuations Measurementssupporting
confidence: 55%
“…4. The cold upwelling events occur much more frequently at Frenchman's Bay than were reported in the study site of Rueda and Cowen (2005), located in Little Sodus Bay on the southeast side of Lake Ontario. As the prevailing winds are from the west, the warm epilimnion is forced to the south by the Coriolis forces with an upwelling of cold water in the region near Toronto.…”
Section: Thermal Exchange Driven By Temperature Differences Between Fcontrasting
confidence: 54%
See 2 more Smart Citations
“…Most of the studies, especially unpublished papers of the French authorities, are focused on the temperature continuum stream-pond-stream, without knowing the heat content behaviour inside the pond. In lake's study, the horizontal scale getting more important and some studies took spatial measurements about great lakes (Xing et al, 2012;Wang et al, 2014), the embayment of lakes, especially about lake Ontario (Rueda & Cowen, 2005;Murphy et al, 2012) or also about a big mire system (Ramos, 2012), without taking into consideration the ponds, where the application should be the most achievable. It is a very important point regarding the ponds, where it is possible to choose the depth of the outflow (monk, weir…) or to change the localization of the outfall in order to decrease the temperature's impact on downstreams.…”
Section: Introductionmentioning
confidence: 99%